Zoonotic risk for Pet Owners in Kathmandu, Nepal (Global Journal of Medical Research, 2020)
Pet keeping practices have a long history in human societies, butpoor knowledge regarding pet keep ingincreases risk of several zoonoses. The aim of this study is to identify the risk of zoonoses based on knowledge, practices, and perception of threat among pet owners in Kathmandu. A cross-sectional questionnaire based study was conducted on 143 purposively selected pet owners from different three wards in Kathmandu metropolitan. Most of the respondents 86.7% (n=143) were keeping dog as a pet in their households. Feeding practices for pet was varied based on economic status where almost a fifth (18%) owners feeding readymade food. The purpose of pets keeping found diverse where most of them kept forpurpose of household security (37.76%). All respondents were literate among them 88.11% of respondents had above secondary level qualifications. The majority of respondents received information from radio/television (92.30%) .
Keywords: zoonoses; pet keeping; education; kathmandu; perception; owners